ANALYSIS OF SOIL CHEMICAL CHARACTERISTICS IN PABATU SERDANG BEDAGAI UNIT OIL PALM PLANTATIONS - Dedi Simanjuntak; Budi Hendrawan (ITScience (Information Technology and Science), 2022)
Soil is a natural medium that is one aspect of supporting the life of all living things, including plants. Soil chemical properties greatly affect the growth process of oil palm plants, especially in the production process of oil palm fruit bunches. The purpose of this study was to determine the soil's chemical properties in oil palm plantations. The method used in this study is a descriptive method by conducting surveys and laboratory analysis. Soil samples were taken randomly at a depth of 0-20cm at four points of plantation land. Several parameters have been analyzed, such as pH, total N, CEC and exchangeable Al (Al-dd). Soil samples were analyzed at the Laboratory of Soil Research Indonesian Oil Palm Research Institute (PPKS) Medan. Determination of the criteria for assessing soil chemical properties based on the soil fertility standards issued by the Soil Research Center (BPT) Bogor (2009). The results of the analysis showed that the soil pH was slightly acidic, total N was low, CEC was low and Al-dd was very low.